Agility training in young elite soccer players: promising results compared to change of direction drills - Chaalali, A.; Rouissi, M.; Chtara, M.; Owen, A.; Bragazzi, N. L.; Moalla, W.; Chaouachi, A.; Amri, M.; Chamari, K. (Biology of Sport, 2016)
The aim of this study was to compare the effect of two different training programmes - change of direction (COD) vs. agility (AG) - on straight sprint (SS), COD and AG test performances in young elite soccer players. Thirty-two soccer players (age: 14.5±0.9 years; height: 171.2±5.1 cm; body mass: 56.4±7.1 kg, body fat: 10.3±2.3%) participated in a short-term (6 weeks) training study. Players were randomly assigned to two experimental groups - training with change of direction drills (COD-G, n=11) or using agility training (AG-G, n= 11) - and to a control group (CON-G, n=10). All players completed the following tests before and after training: straight sprint (15m SS), 15 m agility run with (15m-AR-B) and without a ball (15m-AR), 5-0-5 agility test, reactive agility test (RAT), and RAT test with ball (RAT-B). A significant group effect was observed for all tests (p<0.001; ?2=large). In 15m SS, COD-G and AG-G improved significantly (2.21; ES=0.57 and 2.18%; ES=0.89 respectively) more than CON-G (0.59%; ES=0.14). In the 15m-AR and 5-0-5 agility test, COD-G improved significantly more (5.41%; ES=1.15 and 3.41; ES=0.55 respectively) than AG-G (3.65%; ES=1.05 and 2.24; ES=0.35 respectively) and CON-G (1.62%; ES=0.96 and 0.97; ES=0.19 respectively). Improvements in RAT and RAT-B were larger (9.37%; ES=2.28 and 7.73%; ES=2.99 respectively) in RAT-G than the other groups. In conclusion, agility performance amongst young elite soccer could be improved using COD training. Nevertheless, including a conditioning programme for agility may allow a high level of athletic performance to be achieved.